Tendência das alterações legislativas pós constituição de 1988: valorização partidária ou individualismo? - Mendonça, Larissa Garcia Barbosa (2017)
The research intents to identify if constitutional changes made after 1988 Constitution’s promulgation indicates a tendency to institutionalize the party system or reinforce individualistic behavior. From a neo-institutionalist perspective, it is believed that the analysis of the country's formal rules is an indispensable source for understanding the paths that the party system has taken. In order to answer the question, the original text of the Constitution that relates to the subject was described before any amendment and analyzed the constitutional amendments and decisions of the Federal Supreme Court that could alter in any way the party’s dynamics. The data show that the changes throughout the almost 30 years of the Constitution, are not linear, sometimes favoring individualistic behavior, or strengthening political parties. However, as the final balance of constitutional changes, we found that political parties would emerge as a stronger institution.